Is Notice of Copyright Necessary in Works Published Abroad?—A Query and a Quandary - Arthur S. Katz (Washington University Law Quarterly, 1953)
Every field of law has its “twilight zones,” those areas where ambiguous statutes, contradictory decisions and dearth of authority make for uncertainty and confusion. American copyright law is singularly possessed of many such “twilight zones.” The writer has undertaken this article in the hope that his comments may illuminate (and perhaps, eliminate) the shaded area concerning the eligibility for copyright protection of works initially published abroad without notice of copyright.
Keywords: Copyright